Serum Cytokine Profile by ELISA in Patients with Echinococcal Cysts of the Liver: A Stage-Specific Approach to Assess Their Biological Activity - Luca Piccoli; Valeria Meroni; Francesca Genco; Francesca Tamarozzi; Carmine Tinelli; Carlo Filice; Enrico Brunetti (Clinical and Developmental Immunology)
To investigate the usefulness of serum cytokine dosage in the clinical management of cystic echinococcosis (CE), we analyzed serum levels of Th1 and Th2 cytokines in patients with hepatic CE in different cyst stages, CE1-2 (active), CE3a-3b (transitional), and CE4-5 (inactive). Ex vivo assessment of Th1 (IFN-γ) and Th2 (IL-4, IL-13, and IL-10) cytokines in sera was carried out using ELISA. IL-10 was undetectable in all serum samples of patients and controls, while a few sera contained measurable amounts of IFN-γ, IL-4, and IL-13. No statistically significant difference was found between the percentages of positive samples for each cytokine and the different groups analyzed (patients/controls, stage, number, location, and size of the cyst, serology, and sex of patients), with the exception of the association of IL-4 and IL-13 with the cyst stage. Overall, this investigation showed many limits of serum cytokine dosage as a marker of biological activity of echinococcal cysts. Because of low sensitivity and lack of specificity of this test, we believe that other ways to evaluate ex vivo biological activity of the cysts should be explored.